Efficient Graph Coloring with Parallel Genetic Algorithms - Kokosiński, Zbigniew; Kwarciany, Krzysztof; Kołodziej, Marcin (Computing and Informatics, 2012)
In this paper a new parallel genetic algorithm for coloring graph vertices is presented. In the algorithm we apply a migration model of parallelism and define two new recombination operators SPPX and CEX. For comparison two problem-oriented crossover operators UISX and GPX are selected. The performance of the algorithm is verified by computer experiments on a set of standard graph coloring instances.